The Impact of Extension Teaching Strategies on Small-Scale Farmers' Adoption of Better Rice Varieties(FAROS) in Badeggi Area of Katcha LGA Niger State - Dauda, Nma (BADEGGI JOURNAL OF AGRICULTURAL RESEARCH AND ENVIRONMENT, 2023)
The study looked at the impact of extension education on farmers in Badeggi area of Katcha local government, Niger State adopting rice cultivars, particularly FAROS. A multi-stage random sample procedure was used to select 160 farmers from five villages within the Katcha local government in order to achieve the study's objectives. Descriptive statistics, multiple regression analysis, and the T-test were used to examine the collected data. According to the results, 48.5% of the farmers of enhanced rice varieties were in the active age range of 30 to 40 years. In the study area, the most effective way to instruct farmers planting improved rice varieties was through demonstration (SPART), which accounted for 43.8% of the total. The results of the regression analysis showed that, among the variables influencing farmers' output, land size, adoption rate, and educational attainment were all statistically significant and positively correlated with their output. The T-test result for adopters of enhanced rice varieties and non-adopters was also statistically significant (2.579) at the 5% level. The respondents' issues in the study area included insufficient communication channels, a lack of technical understanding about enhanced rice varieties, and challenges getting improved seed kinds. The respondents' issues in the study area included insufficient communication channels, a lack of technical understanding about enhanced rice varieties, and challenges getting improved seed kinds.